Analisis Terhadap Peraturan Mahkamah Agung Republik Indonesia Nomor 2 Tahun 2022 Dan Penerapannya Ditinjau Dari Perlindungan Hukum Pihak Ketiga Yang Beritikad Baik Pada Penetapan Nomor: 02/Pid.Sus/Keberatan/TPK/2022/PN.Jkt.Pst. - Jihan Sekar Putri (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to determine, analyze, and observe legal protection for Third Parties in Good Faith in PERMA No. 2 of 2022 as well as in its application to the Determination of Objection Number: 02/Pid.Sus/Kebatasan/TPK/2022/PN.Jkt.Pst. This study is a normative legal study using the statutory regulatory approach method and the conceptual approach. This study concludes that the existence of PERMA No. 2 of 2022 as a filler of legal gaps has not provided optimal legal certainty for Third Parties in Good Faith. As Article 1 paragraph (3), Article 7, and the transitional provisions of Article 24 paragraph (4) do not provide full legal protection for Third Parties in Good Faith. This study also found that in its application PERMA No. 2 of 2022 has provided protection for Third Parties in Good Faith in Objection Determination Number: 02/Pid.Sus/Kebatasan/TPK/2022/PN.Jkt.Pst. Third Parties in Good Faith in the consideration of the determination refer to Article 1 paragraph (3) regarding parties who can file objections. Third Parties in Good Faith can recover their belongings as long as they can prove that they are not legally connected to the crime of corruption.